Altered Mitochondrial Respiration and Other Features of Mitochondrial Function in Parkin-Mutant Fibroblasts from Parkinson’s Disease Patients - William Haylett; Chrisna Swart; Francois van der Westhuizen; Hayley van Dyk; Lize van der Merwe; Celia van der Merwe; Ben Loos; Jonathan Carr; Craig Kinnear; Soraya Bardien (Parkinson's Disease)
Mutations in the parkin gene are the most common cause of early-onset Parkinson’s disease (PD). Parkin, an E3 ubiquitin ligase, is involved in respiratory chain function, mitophagy, and mitochondrial dynamics. Human cellular models with parkin null mutations are particularly valuable for investigating the mitochondrial functions of parkin. However, published results reporting on patient-derived parkin-mutant fibroblasts have been inconsistent. This study aimed to functionally compare parkin-mutant fibroblasts from PD patients with wild-type control fibroblasts using a variety of assays to gain a better understanding of the role of mitochondrial dysfunction in PD. To this end, dermal fibroblasts were obtained from three PD patients with homozygous whole exon deletions in parkin and three unaffected controls. Assays of mitochondrial respiration, mitochondrial network integrity, mitochondrial membrane potential, and cell growth were performed as informative markers of mitochondrial function. Surprisingly, it was found that mitochondrial respiratory rates were markedly higher in the parkin-mutant fibroblasts compared to control fibroblasts (p = 0.0093), while exhibiting more fragmented mitochondrial networks (p=0.0304). Moreover, cell growth of the parkin-mutant fibroblasts was significantly higher than that of controls (p=0.0001). These unanticipated findings are suggestive of a compensatory mechanism to preserve mitochondrial function and quality control in the absence of parkin in fibroblasts, which warrants further investigation.